The role of LKS Bipartite to improve company performance - PURWANTO, AGUS (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The problem of employment in Indonesia is very complex, in addition to the laws and regulations on employment that are still overlapping, Indonesia is also the first Asian country to ratify all eight fundamental conventions, including freedom of association and the right to collective bargaining, freedom of association and protection of the right to organize; elimination of forced labor, elimination of discrimination; minimum age, elimination of child labor. Although in reality, many companies have not been able to eliminate these things because of the environment or other things. Facing the problem of human resources or workers, it is necessary to consider how productivity can be achieved by workers. The design of this study is Literature Review, Literature review studies are used to collect data or a synthesis of sources related to the research topic from various sources, including journals, books, documentation, the internet and libraries. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials. The method of searching for articles in research journal databases and searching via the internet. The database search used was Google Scholar from 2019 to 2024. For article searches, the keywords used were also included in the data collection, namely "Bipartite LKS to improve performance". The process of institutionalizing Bipartite LKS as an instrument for preventing industrial relations disputes in the workplace is important and occupies a strategic position. This is based on the natural conditions that trigger the emergence of industrial relations disputes, namely the failure to reach a compromise on certain interests of the parties in the production process in the workplace. Bipartite LKS is effective as a medium for bringing together conflicting interests to be compromised, there is a dialogue process that is oriented towards reaching an agreement on the disputed issues. The obstacles faced in institutionalizing Bipartite LKS as an instrument for preventing industrial relations disputes in the workplace include the lack of support from the Employer to form Bipartite LKS in the Workplace, resistance from Trade Union Organizations/Labor Unions at the Company Level, Bipartite LKS not being a formal institution for Resolving Industrial Relations Disputes, and difficulties in Recruiting Bipartite LKS Management for Workers.